The Future of Television Work in the Light of Artificial Intelligence Challenges an Exploratory Study - Obaid, Mohaned Hameed (ALBAHITH ALALAMI, 2023)
This research examines the future of television work in light of the challenges posed by artificial intelligence (AI). The study aims to explore the impact of AI on the form and content of television messages and identify areas where AI can be employed in television production. This study adopts a future-oriented exploratory approach, utilizing survey methodology. As the research focuses on foresight, the researcher gathers the opinions of AI experts and media specialists through in-depth interviews to obtain data and insights. The researcher selected 30 experts, with 15 experts in AI and 15 experts in media. The study reveals several findings, including the potential use of machine learning, deep learning, and natural language generation techniques in media work. AI aids television broadcasters in detecting fake news, generating news stories, and improving the quality of broadcasting and transmission. However, significant challenges arise when integrating AI technologies into television, such as the need for a specialized professional and programmatic workforce in the field of information technology.